2020
DOI: 10.1002/mbo3.1023
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an antimicrobial‐resistant, biofilm‐forming, Klebsiella grimontii isolate from a reusable water bottle

Abstract: A reusable water bottle was swabbed as part of the citizen science project “Swab and Send,” and a Klebsiella grimontii isolate was recovered on chromogenic agar and designated SS141. Whole‐genome sequencing of SS141 showed it has the potential to be a human pathogen as it contains the biosynthetic gene cluster for the potent cytotoxin, kleboxymycin, and genes for other virulence factors. The genome also contains the antibiotic‐resistant genes, blaOXY‐6‐4, and a variant of fosA, which is likely to explain the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…grimontii (). Hubbard et al [20] recently reported on a strain of K. grimontii that encoded the BGC, based on antiSMASH analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…grimontii (). Hubbard et al [20] recently reported on a strain of K. grimontii that encoded the BGC, based on antiSMASH analysis.…”
Section: Discussionmentioning
confidence: 99%
“…michiganensis clinical isolates, the reference sequence [11], a recently described K. grimontii sequence [20] and a homologous sequence found in Pectobacterium brasiliense BZA12 (to be used as an outgroup in later phylogenetic analyses; identified as encoding the complete kleboxymycin BGC through NCBI BLASTP). Phylogenetic analyses were carried out on the MSA using the R package Phangorn v2.5.5 [21], producing a maximum-likelihood tree, which was visualised and rooted (on P.…”
Section: Methodsmentioning
confidence: 99%
“…The protein sequences encoded in the BGC were extracted from the annotated assemblies using samtools v1.9 faidx (19) and concatenated into a single sequence (the sequence data are available as supplementary material from figshare). These concatenated sequences were used to produce a multiple-sequence alignment (MSA) in Clustal Omega v1.2.4, along with the BGC sequences of the three K. michiganensis clinical isolates, the reference sequence (11), a recently described K. grimontii sequence (20) and a homologous sequence found in Pectobacterium brasiliense BZA12 (to be used as an outgroup in later phylogenetic analyses; identified as encoding the complete kleboxymycin BGC through NCBI BLASTP). Phylogenetic analyses were carried out on the MSA using the R package Phangorn v2.5.5 (21), producing a maximum-likelihood tree, which was visualised and rooted (on P. brasiliense BZA12) using the Interactive Tree of Life (iTOL v5.5) (22).…”
Section: Characterization Of the Kleboxymycin Bgc In Genomesmentioning
confidence: 99%
“…Given the work detailed above had detected the kleboxymycin BGC in several different but closely related Klebsiella species and in a range of clinical and gut-associated isolates, and Hubbard et al(30) recently detected the BGC in a strain of K. grimontii, we chose to increase the scope of our analysis to include 7,170 publicly available assembled Klebsiella genomes (including our three clinical strains, and five isolates from preterm infants (1)) (Supplementary Table 1). NCBI annotations for genomes are improving, we have noted issues with identities attributed to Klebsiella genomes (1).…”
mentioning
confidence: 99%
“…These are uploaded onto the dedicated Facebook project webpage [ 11 , 12 ] with an explanation of the results, highlighting interesting hits we have found. Further updates are provided as the project moves forward, both in terms of results (e.g., we have recently included a post about a multidrug resistant Klebsiella grimontii strain isolated from a reusable water bottle [ 13 ]) and significant developments in the antibiotic resistance and chemotherapy. This serves as a permanent historical record of all the project activity since its launch and as a useful repository for important reports on antimicrobial resistance.…”
mentioning
confidence: 99%